Comparison of modelling and measurement results of spectra emitted by a programmable lamp - Feldzensztajn, Mateusz; Mazikowski, Adam (Photonics Letters of Poland, 2018)
Nowadays artificial light with optimized spectrum is used in many different applications. For instance, it is widely used in museums and exhibitions to illuminate the art. Moreover, such light stimulates the growth of plants, or can be applied in industry and healthcare. To achieve the best results for each application, adjusting of dedicated spectrum is required, that is a complicated task. The ongoing research is focused on simplifying this process. In this paper we present the developed lamp with programmable spectrum, and its user interface. Predicted and measured output spectra are investigated. Full Text: PDF References Mottier, P., LEDs for Lighting Applications, Willey (2009) CrossRef Pimputkar, S., Speck, J.S., DenBaars, S.P., Nakamura, S., "Prospects for LED lighting", Nature photonics 3 (4), 180 (2009) CrossRef Knulst, A. J., Mooijweer, R., Jansen, F. W., Stassen, L. P., and Dankelman, J., "Indicating shortcomings in surgical lighting systems," Minim. Invasive Ther. Allied Technol. 20 (5), 267–275 (2011) CrossRef Blaszczak, U., Gryko, L., Palkowska, A., Kulesza, E., Zajac, A., "Color mixing in LED illuminating system for endoscopic purposes", Lighting Conference of the Visegrad Countries (Lumen), IEEE (17 November 2016) CrossRef Nanya, K., Ishigami, Y., Hikosaka, S., Goto, E., "Effects of blue and red light on stem elongation and flowering of tomato seedlings", Acta Hortic. 956, pp. 264–266 (2012). CrossRef Cegielski, T. , Bujalski, D. , Kowalczyk, K. , Gajc-Wolska, J. , Hemka, L., "Use of light emission programming in tomato grow light system", Proceedings of Electrotechnical Institute 63 (273), 79-94 (2016) CrossRef Mazikowski, A., Feldzensztajn, M., "Lamp of adjustable spectrum for photographic usage", Proc. SPIE 10445, Photonics Applications in Astronomy, Communications, Industry, and High Energy Physics Experiments, 104450K (2017) CrossRef CREE Inc, Cree® XLamp® XT-E LEDs Product family data sheet (accessed 16 April 2018). DirectLink Dyble, M., Narendran, N., Bierman, A., Klein, T., "Impact of dimming white LEDs: chromaticity shifts due to different dimming methods", Optics and Photonics 2005, San Diego, California, United States DirectLink